Catch Production Data Information System and Fish Auction at UPT PPP Pondokdadap - Vivian Kudrati, Amelinda; Isdianto, Andik (Universitas Airlangga, 2024)
Sendang Biru beach is facing directly to the Indian Ocean, an area with abundant fishing potential. People working as fisherman make Sendang Biru is a fishing ground. Fishing ports play an important role in the development of every activity related to fisheries, especially capture fisheries. The fishing port is a place for government activities in the field of fisheries, such as loading and unloading of fish. Unit Pelaksana Teknis Pelabuhan Perikanan Pantai (UPT PPP) Pondokdadap is one of the coastal fishing ports with the largest landing of fish, especially tuna, tuna, and skipjack in Malang. Fishery production results are obtained from fishing by fishermen in the sea. The types of fish mostly found in Sendang Biru are dominated by large pelagic fish, namely tuna. Fishing production is obtained from fishermen's catches with fishing gear in the form of purse seines and handlines. A lifeboat with handline fishing gear is the fleet used to catch large pelagic fish. Total fishery production from production volume and production value on January 1 to June 30, 2022 obtained results on fishery production volume reaching 5,596,271 kg with fishery production value reaching Rp. 137,691,524,000. There are several obstacles during the fishing process regarding bad weather or rainfall with high waves, which can affect fishermen's income in fishing activities classified as low.